ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA MELALUI PEMBELAJARAN SETS KELAS X PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Nofia Nur Miftianah; Andari Puji Astuti; Fitria Faticahtul Hidayah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Thinking skills so important to student, to drive in the attitude of students in socializing and can be upgraded early in grade X. with the achievement of a good learning process, students are able to recognize critical thinking skills so that they can create an atmosphere of learning activities. This research examines the critical thinking skills of students in grades XI IPA SMA N 09 Semarang. The purpose of this research was to find out how the achievement of critical thinking skills of students bervisi SETS Xgrade material a non electrolyte and electrolyte solution. The vision SETS can help students learn quickly and efficiently so that makes it easy to scientifically study chemistry with apply it in everyday life. The subject is a student of class X of SCIENCES 6 high school N 9. The methods used in this research is descriptive method. This research essay tests eassesment instrumentsusing critical thingking skills the vision SETS. The research results obtained are achievement test essays critical thingking skills the vision SETS have a score of eight indicators.Keywords: critical thinking skills, the vision SETS, assessment instruments